Penguasaan Konsep Usaha Dan Energi Peserta Didik Kelas X Dengan Model Pembelajaran Ekspositori Berbantuan Organizers - Dwi Gita Oktaviani; Ahmad Harjono; I Wayan Gunada (Department of Physics Education, Universitas Mataram, 2018)
Lesson material presented in the form of data or facts and specific concepts on expository learning model helps learners to connect new material with material that precedes it, so organizers help is provided to instill meaningful learning. This study aims to determine the difference of influence of the implementation of learning model of assisted advance organizer and post organizer expository. The population in this study is all students of class X MIA SMA Negeri 3 Mataram academic year 2017/2018. Sampling is done by purposive sampling technique, and quasi experimental research uses non-equivalent control group design with pre-test-and post-test. The results obtained from the classroom given the treatment of expository learning model assisted by advance organizer and post organizer have the same tendency improvement. In both classes there is a relatively similar increase in the mastery of the previous concept, but the difference between the two is not much different. Therefore, there is no difference of influence between expository model of assisted advance organizer and post organizer to the mastery of work and energy concepts of learners.